MPO interacts with hRSV particles, contributing to the virucidal effects of NETs against clinical and laboratory hRSV isolates - da Silva Pinto, Leonardo [UNESP]; Junior, Ronaldo Silva Alves [UNESP]; Lopes, Bruno Rafael Pereira [UNESP]; da Silva, Gabriel Soares [UNESP]; de Lima Menezes, Gabriela; Moreira, Pedro; de Oliveira, Juliana [UNESP]; da Silva, Roosevelt Alves; Lousa, Diana; Toledo, Karina Alves [UNESP] (Elsevier, 2024)
Human Respiratory syncytial virus (hRSV) mainly affects immunosuppressed patients requiring hospitalization. No specific treatment is financially accessible, and available vaccines do not cover all risk groups. During hRSV infection, there is a robust neutrophilic influx into the airways. hRSV-activated neutrophils release substantial neutrophil extracellular traps (NETs) in lung tissue, comprising DNA, histones, cytosolic, and granular proteins. NETs form mucus buildup in the lungs, compromising respiratory capacity and neutralizing viral particles. Understanding responsible NETs molecules requires improvement. We evaluated NETs interacting with hRSV particles and their contribution to anti-hRSV NET effects. Immunoblotting, immunoprecipitation, and peptide sequencing assays confirmed hRSV binding to a 50–75 kDa NET protein, Myeloperoxidase (MPO). MPO, a microbicide enzyme in NETs, interacts with hRSV, likely at F0 protein (site IV) on the viral surface. Additionally, MPO (32 μM) and NETs (0.4 μg/mL) reduced in vitro replication of clinical (hRSV A and B) and laboratory (Long) hRSV isolates by approximately 30 %, reversible by selective MPO inhibitor (PF-06281355; 48 μM). Thus, MPO contributes to virucidal NET effects on diverse hRSV strains, enhancing comprehension of NETs' role in infection and aiding treatment strategies for respiratory diseases.
Keywords: Antiviral; Enzyme; Microbicidal; Neutrophils; Syncytial